Data Protection Impact Assessment (DPIA) sebagai Instrumen Kunci Menjamin Kepatuhan UU PDP 2022 di Indonesia - Filal Khair; Sidi Ahyar Wiraguna (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid digital transformation in Indonesia has intensified the need for robust personal data protection, particularly through the mechanism of the Data Protection Impact Assessment (DPIA) as stipulated in Law Number 27 of 2022 concerning Personal Data Protection (PDP Law). This study employs a normative juridical and qualitative approach to examine the role of DPIA as a key instrument in identifying, evaluating, and mitigating privacy risks in high-risk personal data processing activities. The findings reveal that although DPIA represents a significant normative advancement, its implementation faces major challenges, including the absence of detailed technical regulations, limited institutional capacity, and insufficient data subject involvement. By comparing international best practices, this research highlights the urgent need to strengthen regulatory frameworks, enhance digital and privacy literacy, and develop a collaborative ecosystem to optimize the DPIA function. Normative recommendations are formulated to reinforce DPIA as a risk management tool and a safeguard for privacy rights, aiming to foster a secure and trustworthy digital ecosystem amid ongoing digital transformation.